Effect of the low-intensity pulsed ultrasound therapy on healing of Achilles tendinopathy in a rat model - Kurtulmus, Tuhan; Celebi, Mehmet Emin; Bektas, Ebubekir; Arican, Cigdem Dicle; Kucukyildirim, Bedri Onur; Demirkol, Metehan (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2024)
Objective: This study aimed to investigate the effect of the low -intensity pulsed ultrasound (LIPUS) on the healing of Achilles tendinopathy in a rat model induced by type 1 collagenase. Methods: The study was conducted on 144 Achilles tendons of 72 Wistar albino female rats with typical activity and weighing 300-350 g. The model of Achilles tendinopathy was created by injecting type 1 collagenase. According to the sampling time, 4 groups served as the control group, while 8 groups received treatment at varying periods. Low -intensity pulsed ultrasound therapy was initiated in 8 groups at 1, 7, and 15 days. Treatment was extended for 1 and 2 weeks. Achilles tendons were removed from the treatment and control groups on the 15th, 21st, 30th, and 45th days for biomechanical and pathologic examination. Results: Compared to the control groups, LIPUS treatment administered in the first days of the proliferation phase increased tensile strength by approximately 30%, modulus of elasticity by approximately 53%, fibrillar appearance by 53%, and inflammation by 53%-33% in a shorter time. It was also demonstrated that starting treatment in the first days of the proliferation phase resulted in comparable success even with 1 -week treatment compared to 2 -week treatment. Conclusion: Low -intensity pulsed ultrasound therapy can provide positive results in managing Achilles tendinopathy in the rat model. Its capacity to shorten recuperation time has piqued the interest of conservative treatment approaches. As a result, more clinical research is required.
Keywords: Low-intensity pulsed ultrasound; Rat; Collagenase type 1; Tendinopathy; TEMPERATURE-CHANGES; TENDON; REPAIR; Orthopedics